You better listen to yourself: studying metacognitive efficiency in emotion recognition by voice - Sinvani, Rachel-Tzofia; Fogel-Grinvald, Haya (Frontiers in Communication, 2024)
Purpose: Metacognition, or the ability to monitor the performance of oneself, is known for its fundamental importance for human behavior adjustments. However, studies of metacognition in social behaviors focused on emotion recognition are relatively scarce. To fill this gap, here,In the current study, we aimed to examine the effectiveness of metacognition, measured by self-rated confidence in voice emotion recognition tasks within healthy individuals. Methods: We collected 180 audio-recorded lexical sentences portraying discrete emotions: anger, happiness, sadness, fear, surprise, and neutrality expressions. Upon listening to voice stimuli, participants (N=100; 50 females, 50 males) completed the perception task of recognition of emotion. After each trial, a confidence rating (CR) was assigned. Results: A series of one-tailed t-tests showed that the differences in mean CRs assigned to correct and incorrect performances were significant for all emotions and neutral expression. Conclusions: Our preliminary results demonstrate efficiency in metacognitive emotion recognition by voice. Theoretically, our results support the difference between accuracy in metacognition, measured by CR, and efficiency in metacognition, as it specified the CR between correct and incorrect performance. To gain better insights into practical issues, further studies are needed to examine whether and what are the differences between accuracy and efficiency in metacognitive, as part of social communication.